Commerce et Constitution : une analyse de la stratégie de marchandage dans l'Accord canado-américain de libre-échange - Lusztig, Michael (Études internationales, 1995)
This paper attempts to explain the controversial, and politically risky, Canada-us Free Trade Agreement (CUFTÀ) as a by-product of political entrepreneurship in pursuit of electoral realignment. Upon becoming Prime Minister of Canada in 1984, Brian Mulroney harbored one overriding ambition : to engineer electoral realignment whereby his Conservative Party would supplant the Liberals as the dominant federal party in Quebec, and by extension, in Canada. Mulroney sought realignment by satisfying Quebec's fundamental institutional demands, which took the form of the Meech Lake constitutional Accord. This objective necessitated the construction of a coalition that married the trade and constitutional issues. Mulroney's brokerage skills ensured that CUFTA progressed in tandem with Meech Lake as a means to realizing his first-order objectives.